ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE DI KANTOR SAMSAT AMURANG - Tulle, Synta; Sondakh, Jullie J.; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
This research aims to know the implementation of good governance principles at Samsat Amurang office. Principles relating to the financial statements are the principle of fairness, accountability principles, principles of transparency, and the principle of responsibility. This study uses a qualitative method. This research was conducted by interviewing the head of UPTBÂ Samsat Amurang office and treasurer of reception section. Based on the results of research implementation of the principle of good governance are the principle of fairness, accountability principles, transparency principles, and running well in accordance with the procedures and rules applicable, while the application of the principle of responsibility is about the comfort of society that still can not satisfy the community and not in accordance with the rules of the good application of responsibility principle. Keywords: good governance